Observasi cara pengolahan sampah rumah makan di Gegerkalong Hilir Bandung - Alma Aliya Jacinda; Surtikanti , Hertien (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Food waste is a never-ending issue in every country, including Indonesia. Food waste is identical to leftovers from restaurants. The more restaurants there are, the more waste is generated. This observation was carried out in Gegerkalong Hilir which is one of the areas in Gegerkalong Village. This area is one of the most densely populated areas because it is close to three large campuses. This research is a qualitative research. The aim of this research is to find out the waste processing system implemented in restaurants and the efforts made by restaurants to overcome waste problems.